Posterior Cervicothoracic Stabilization Using Tapered Rods - Mohamed Elqazaz (Egyptian Spine Association, 2015)
Background Data: The cervicothoracic spine is a junction area with complex biomechanics. A variety of disorders affect this region, rendering it unstable. Numerous posterior constructs have been evaluated. The clinical efficacy of a screwrod system utilizing tapered (dual-diameter) rods in cervicodorsal stabilization is still not evident. Purpose: Our aim is to evaluate the clinical efficacy of dual diameter rods (5.5– 3.5mm taper), connecting 3.5-mm cervical lateral mass screws/pedicle screws and 5.5-mm thoracic pedicle screws used to instrument across the cervicothoracic junction for a variety of pathologies. Study Design: A retrospective descriptive clinical case study. Patients and Methods: The authors retrospectively reviewed their archive between February 2011 and February 2015, and ten patients who were operated upon due to cervicothoracic junction pathologies were included. All patients underwent surgical treatment by posterior instrumentation utilizing tapered rods. The cases were periodically followed up. Results: There were six men and four women included in the study, with a mean age of 40 years (range 21–62 years). There were five cases of trauma, two cases of tuberculosis and three cases of spine metastasis. Seven patients experienced marked improvement of their preoperative weakness according to Frankel grades of paraplegia. All patients showed stable cervicodorsal junction with fusion after one year. Three patients suffered postoperative wound infection. Conclusion: Tapered rods are an excellent and a viable option to connect screws to stabilize cervicothoracic junction. (2015ESJ089)